Effects of Glucosamine-Chondroitin, Chitosan, and Phytoestrogen on Knee Osteoarthritis Inflammatory and Cartilage Degeneration Biomarkers and Clinical Symptoms in Postmenopausal Women - P. Kermawan; I.W.P.S. Yasa; M. B. Karna; S. Herawati; I. K. Suyasa; N.L.K.A. Arsani; K. E. Calisto; K.S.S. Yogananda; K.S.S. Wiwekananda; N.S.N. Wijaya; I. M. Jawi (Genij Ortopedii, 2026)
Introduction Knee osteoarthritis (OA) is a progressive disease causing pain and dysfunction in postmenopausal women. Purpose This study aimed to evaluate the therapeutic efficacy of a combination of glucosamine-chondroitin, chitosan, and phytoestrogen with paracetamol compared to paracetamol alone in postmenopausal women with knee osteoarthritis. Materials and Methods A double-blind randomized controlled trial was conducted on 60 postmenopausal women with Kellgren – Lawrence grade II–III knee osteoarthritis. A total of 60 patients were included in this study and divided into treatment and control groups with a 1:1 ratio. The mean age of patients was 59.77 years (± 2.99) while the control group had a mean age of 60.4 years (± 3.21), there was no significant difference (p = 0.43). Patients were randomly assigned into two groups: the treatment group (n = 30), which received glucosamine-chondroitin, chitosan, and phytoestrogen in combination with paracetamol, and the control group (n = 30), which received paracetamol alone. The levels of soluble interleukin-6 receptor (sIL-6R), interleukin-10 (IL-10), cartilage oligomeric matrix protein (COMP), as well as Visual Analog Scale (VAS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were measured at baseline and after two weeks of treatment. Results After the pharmacological intervention, the treatment group showed significant reductions in WOMAC score, COMP, and sIL-6R compared to the control group (p < 0.01). Both groups had increased IL-10 levels following treatment, but the increase was greater in the control group. Discussion The combination therapy demonstrated improvement in joint function and a reduction in inflammatory and cartilage degeneration markers. These findings support the anti-inflammatory and chondroprotective potential of natural compounds in the management of knee osteoarthritis. Conclusion The combination of glucosamine-chondroitin, chitosan, phytoestrogen, and paracetamol demonstrated superior short-term effects in reducing inflammatory and cartilage degeneration biomarkers and improving clinical symptoms in postmenopausal women with grade II-III knee osteoarthritis compared with paracetamol alone.